The ThSOS3 Gene Improves the Salt Tolerance of Transgenic Tamarix hispida and Arabidopsis thaliana - Liu, Zhongyuan; Xie, Qingjun; Tang, Feifei; Wu, Jing; Dong, Wenfang; Wang, Chao; Gao, Caiqiu (Frontiers in Plant Science, 2021)
The SOS (salt overly sensitive) signal transduction pathway is one of the most highly studied salt-tolerant pathways in plant. However, the molecular mechanism of the salt stress response in T. hispida has remained largely unclear. In this study, 5 SOS genes (ThSOS1-ThSOS5) from T. hispida were cloned and characterized. The expression levels of most of the ThSOS genes were significantly changed after NaCl, PEG6000 and ABA treatments in at least one organ. Notably, the expression of ThSOS3 was significantly downregulated after 6 h under salt stress. To further analyze ThSOS3 function, ThSOS3 overexpression and RNAi-silencing were performed using a transient transformation system. Overexpression of ThSOS3 in transgenic T. hispida plants increased ROS-scavenging capability and antioxidant enzyme activity, decreased malondialdehyde (MDA) and H2O2, and reduced electrolyte leakage rates compared to controls under salt stress. Similar results were obtained in the physiological parameters of transgenic Arabidopsis, including H2O2 and MDA accumulation, SOD and POD activities and electrolyte leakage. In addition, transgenic Arabidopsis plants overexpressing ThSOS3 displayed increased root growth and fresh weight gain under salt stress. Together, these data suggest that overexpression of ThSOS3 confers salt stress tolerance to plants via enhancing the activities of antioxidant enzymes and improving ROS-scavenging capability and decreasing the malondialdehyde content and lipid peroxidation cell membranes. These results suggest that ThSOS3 might play an important physiological role in salt tolerance in transgenic T. hispida plants. This study provides a foundation for further understanding the salt tolerance mechanisms involving ThSOSs in T. hispida.